Improving preference assessment in TOPSIS method for multi-criteria supplier selection problem. (2016) - Azadfallah, Mohammad
The conventional TOPSIS method attempts to choose alternatives that simultaneously have the shortest distance from the positive ideal solution and the farthest distance from the negative-ideal alternative. However, this assumption may not be always valid. It is argued here that both distances must be considered simultaneously. Since, in order to effectively solve this limitation, this paper proposed an extended TOPSIS method to deal with the supplier selection problem. In the proposed method, a final ranking of the feasible alternatives is the intersection of the two descending and ascending ranking, which in TOPSIS method show them by distance to ideal and negative-ideal solution respectively. A comparative analysis is performed, and the proposed method seems to be more satisfactory than the conventional method for solving decision problems. So, in 49% of times (out of 100 cases), two best-ranked alternatives are incomparable, and there is no clear evidence in favour of either of alternatives. However, conventional TOPSIS introduced only one of them as the best (optimal) alternative.